Chemical characteristics of atmospheric particulate matters on pine needles from single particle analysis - TAINOSHO, Yoshiaki; IWASAKI, Misuzu (ENVIRONMENTAL SCIENCE, 2005)
Airborne particulate pollution has increased in the urban area. Black pine seedlings were settled in the eastern part of Kobe city where located in heavy traffic and industrial area. Needles of these seedlings were collected 1, 2, 5 and 8 weeks after settling. Individual particles on the surface of pine needles were observed by using FESEM. The chemical composition was analyzed by single particle analysis. To estimate possible sources of the atmospheric particles in Kobe area, all particles were classified according to their chemical compositions by cluster analysis. Cluster analysis showed five different particle types. They contained many anthropogenic particles, e.g. fly ash particles, iron ball, brake wear and also natural origin sources such as soil particles.